Ocular manifestations for misdiagnosing acute angle closure secondary to lens subluxation - Wang, Xinyu; Wang, Qian; Song, Wenqi; Yang, Yu; Zhang, Ruixuan; Lifen, Gao; Lu, Hui (Frontiers in Medicine, 2024)
Introduction: The objective of this study was to assess the clinical characteristics and biometric parameters by the IOL Master of patients suffering from acute secondary angle-closure caused by zonular dialysis (ASAC-ZD) who were misdiagnosed and acute primary angle closure (APAC).Methods: In this retrospective study, 34 ASAC-ZD and 39 APAC eyes participated. Sex, age, best corrected visual acuity, axial length (AL), anterior chamber depth (ACD), anterior chamber depth standard deviation (ACDSD), lens thickness (LT) and lens thickness standard deviation (LTSD) were measured by IOL Master and compared between the two groups. In addition, the difference in ACD (ACD difference) between the affected eye and the contralateral eye was compared. Logistic regression analysis was performed to determine the predictive factors of lens subluxation. To find the appropriate cut-off value for biometric parameters, ROC curves were constructed to distinguish between ASAC-ZD and APAC and cataract. Results: Compared with the APAC group, the ASAC-